Criticism of human dignity and the notion of “basic necessities” as a possibly better foundation for rights - Sosa Sacio, Juan Manuel (2015)
What is the element in which human rights arebased? What is it that holds the set of rights that belong  to  every human being for the only fact of being such? Confronted with this questions, several different answers have been formulated. In the present, the position in doctrine that statesthat dignity should be the foundation of humanrights is the preferred.In this article, the author presents an alternative answer to these questions. He proposes the “basic human necessities” as the element in which human rights are founded. In order  to  achieve this, he criticizes the aforementioned position, and introduces arguments in favor of the one he defends.